SME’s CLUSTERING AND ITS IMPACTS ON INNOVATION IN INDONESIA: CASE STUDY AT CIBADUYUT, WEST JAVA - Gandhi Pawitan; Theresia Gunawan (Research Report - Humanities and Social Science, 2012)
Globalization is becoming an important issue for most businesses in the world. Since globalization changes business trends and shortens product life cycles, it requires companies to be more innovative in developing new ideas, products and processes. Clustering is one of ways to promote innovation by facilitating sharing information and ideas between firms, attracting buyers and suppliers, and providing opportunities for joint training. Many researches in developed countries found that the proximity between companies facilitated collaboration and provided a more conducive environment for R&D and knowledge sharing which can develop culture of entrepreneurship and innovation. Then, the success of clusters in developed countries has led many government and companies to establish new clusters.Since products from China have been dominated Indonesia’s market share with lower price, it is very difficult for Indonesian Small and Medium Enterprises to compete with lower price also. Therefore, to face the competition, innovation is perhaps as an alternative strategy for Indonesian SMEs. In facts, more than 50% of small and medium enterprises in Indonesia are located in clusters and most of them are located in Java, Bali and Nusa Tenggara. Even though they located in cluster but their innovations still very low and judging from technology perspective, most of them have low level of technologies and still remain in the underdeveloped stage. Therefore, in this research, the author tries to find (1). To what extend do cluster Indonesia promote innovation, (2). To find the reasons why clusters in Indonesia has not been working well in promoting innovation and (3). To investigate what aspects can be improved by Indonesian SMEs to boost their innovation.Keywords: clustering, innovation, small and medium enterprises.